The Impact of Human Resource Practices on Employee Retention in the Telecom Sector - Maqsood Haider; Amran Rasli; Chaudhry Shoaib Akhtar; Rosman Bin Mohammesd Yusoff; Omair Mujahid Malik; Alamzeb Aamir; Ahmed Arif; Shaheryar Naveed; Fariha Tariq (International Journal of Economics and Financial Issues, 2015)
This study examines the human resource practices that promote employee retention. Effective human resource practices can reduce employee turnover and increase retention within an organization. Key employees are the instrument for overall growth and development of an organization. This study focuses on telecom sector of Pakistan. The most important human resource practices have been identified with the help of literature. These practices are training and development, compensation and culture. A questionnaire was developed in this study with the help of literature to measure the identified human resource practices and employee retention. The sample size of this study was 250. Regression analysis was performed to analyse the data. The results of multiple regressions revealed a significant impact of human resource practices on employee retention. Compensation and culture has a positive relationship with employee retention whereas training and development has a negative one. This study guides the management to devise the effective strategies to improve the employee retention.